Global cities, hypermobility, and Covid-19. (March 2022) - da Silva Corrêa, Leandro; Perl, Anthony
Abstract: The relationship between cities, globalization and mobility has produced recurring urban challenges over time. This article examines how mobility networks can turn global cities into Pandemic Gateways. Our hypothesis is that global cities became the gateway by which COVID-19 was introduced to many countries through the hypermobility of infected international travelers. To assess this transmission mechanism, we assembled data about the population and COVID-19 cases in global cities and their associated countries, comparing their infection rates on a fixed date. We demonstrate that most global cities followed a common pattern in the pace and intensity of COVID-19's spread during the first wave of the pandemic. Among our global cities sample, 75% served as the gateway through which COVID-19 was diffused within their respective countries. This trend reached 90% in a subset based upon the urban hierarchy among global cities. Hypermobility, which we demonstrate contributed to the mechanism by which global cities diffused COVID-19 initially, is also correlated with the global cities hierarchy, as supported by air travel data. Our findings suggest the need to appreciate why global cities can serve as gateways of pandemic diffusion, while also seeking to understand why some did not function in this way. Highlights: Most global cities served as COVID-19 gateways to their respective countries. Hypermobility was the force driving COVID-19's global diffusion. Globalization indicators influence international COVID-19 diffusion rates.